An Analysis of Students’ Translation Quality in Translating Hortatory Exposition Text - Vivi Nopila Sari; Rusdi Noor Rosa (Journal of English Language Teaching, 2021)
This research aims at finding out the translation quality and the difficulties faced by the third year students of Universitas Negeri Padang in translating a hortatory exposition text. The data of this research were the translation quality and the difficulties faced in translating a hortatory exposition text entitled Bersama Atasi Covid-19. The data were collected by using a translation test and analyzed by using the TQA model by Sofyan and Tarigan (2019) and four components by Sari (2018). To gain the trustworthiness of the research, this research applies the validator and the raters. The finding shows that translation quality of students in translating hortatory text was 80 in almost completely successful level. There are 18 students (60%) categorized into successful level, 12 students (40%) in almost completely successful level, and no one (0%) in adequate, inadequate, and totally inadequate level. Furthermore, there were three thirteen mistakes found in the finding which grammatical structure is the most frequent mistake made by the students.